Factors Affecting Parents' Knowledge Level In Providing Early Childhood Sexual Education - Lisnawati; Mentari Nur Apriliani (Media Informasi, 2023)
Introduction: In 2017, Indonesia were the most victims of sexual violence in children who were attending kindergarten or elementary school (1,443 children), while in Cirebon Regency there was an increase in the incidence of child sexual violence in 2018 and 2019. The aim : to find out what factors affect the level of knowledge parents in providing early childhood sexual education. Method :Using cross sectional technique, the population is all parents and students who are actively attending school as many as 43 respondents, using total sampling technique. Data analysis used frequency distribution and Chi Square test. Result : The last education of the majority of respondents was secondary as much as 22 (51.2%). The majority of respondents do not work as much as 23 (53.5%). The majority of respondents were exposed to information as much as 31 (72.1%). The knowledge of the majority of respondents is good as much as 35 (81.4%). For bivariate analysis of statistical test results with Chi Square test between the latest education, occupation, and information exposure with the level of knowledge of parents obtained p-values ​​of 0.026, 0.014. and 0.004 (<0.05). Conclusion: There is a close relationship between recent education, employment, and information exposure with parental knowledge in providing early childhood sexual education.